2016
DOI: 10.3390/rs8040313
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Deformation of Sinkholes in Wink, Texas, Observed by Time-Series Sentinel-1A SAR Interferometry (Preliminary Results)

Abstract: Spatiotemporal deformation of existing sinkholes and the surrounding region in Wink, TX are probed using time-series interferometric synthetic aperture radar (InSAR) methods with radar images acquired from the Sentinel-1A satellite launched in April 2014. The two-dimensional deformation maps, calculated using InSAR observations from ascending and descending tracks, reveal that much of the observed deformation is vertical. Our results indicate that the sinkholes are still influenced by ground depression, implyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…Sinkhole inventories are therefore typically built using airborne platforms. It should be noted that the higher spatial resolution (12 m) and absolute vertical accuracy (6 m) of the recently released WorldDEM [75] may be suitable for the compilation of sinkhole inventories, especially for large sinkhole events, for example in the cases where widths exceeding 100 m and depths exceeding 30 m have been reported [4,76]. Studies have found that high quality topographic maps generated using stereogrammetry on orthophotos can be used to detect and delineate surface depressions likely to be related to sinkholes [22].…”
Section: Compilation Of Sinkhole Inventoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinkhole inventories are therefore typically built using airborne platforms. It should be noted that the higher spatial resolution (12 m) and absolute vertical accuracy (6 m) of the recently released WorldDEM [75] may be suitable for the compilation of sinkhole inventories, especially for large sinkhole events, for example in the cases where widths exceeding 100 m and depths exceeding 30 m have been reported [4,76]. Studies have found that high quality topographic maps generated using stereogrammetry on orthophotos can be used to detect and delineate surface depressions likely to be related to sinkholes [22].…”
Section: Compilation Of Sinkhole Inventoriesmentioning
confidence: 99%
“…Their large scale and the relatively small-scale of deformation events lends itself to the successful monitoring by conventional repeat-pass interferometry. However, in the case of cover-collapse type sinkholes, the small scale of sinkholes, usually occupying a couple of pixels compared to other geohazards, imply that they can easily be misinterpreted as noise of processing errors [76], especially when DInSAR approaches are adopted. In the case of subsidence-type sinkholes, despite the relative success in detecting surface deformation using DInSAR, certain limitations were also identified.…”
Section: Detecting Precursors To Sinkhole Developmentmentioning
confidence: 99%
“…2016, 8,376 2 of 12 [8][9][10][11][12] have demonstrated the capability and great potential of S1A TOPS in ground surface deformation monitoring. In contrast to the conventional strip-map or ScanSAR data, multiple consecutive S1A TOPS frames (defined by ESA, where one zip file of S1A TOPS data distributed in Scihub [13] denotes a single frame) can generate long seamless strip data which is 250 km wide.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to a new generation of SAR systems, such as the Sentinel-1A (S1A) [5,6] equipped with the Terrain Observation by Progressive Scans (TOPS) [7], the continent-wide Interferometric Synthetic Aperture Radar (InSAR) measurements becomes possible. Previous studies [8][9][10][11][12] have demonstrated the capability and great potential of S1A TOPS in ground surface deformation monitoring. In contrast to the conventional strip-map or ScanSAR data, multiple consecutive S1A TOPS frames (defined by ESA, where one zip file of S1A TOPS data distributed in Scihub [13] denotes a single frame) can generate long seamless strip data which is 250 km wide.…”
Section: Introductionmentioning
confidence: 99%
“…Sentinel-1A data have since been used to make observations of deformation that is centimetres-to-metres in magnitude, associated with earthquakes (e.g., Mw 7.8 Gorkha, Nepal: [19][20][21][22]); volcanic eruptions (e.g., Fogo, Cape Verde: [23]); and the development of sink holes (e.g., Wink, Texas: [24]). However, the detection of small-magnitude displacements, such as subsidence of the Perth Basin, is reliant on longer time series of images.…”
Section: Introductionmentioning
confidence: 99%